2.4=(3-x)+(3-3x)+x+x

Simple and best practice solution for 2.4=(3-x)+(3-3x)+x+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.4=(3-x)+(3-3x)+x+x equation:


Simplifying
2.4 = (3 + -1x) + (3 + -3x) + x + x

Remove parenthesis around (3 + -1x)
2.4 = 3 + -1x + (3 + -3x) + x + x

Remove parenthesis around (3 + -3x)
2.4 = 3 + -1x + 3 + -3x + x + x

Reorder the terms:
2.4 = 3 + 3 + -1x + -3x + x + x

Combine like terms: 3 + 3 = 6
2.4 = 6 + -1x + -3x + x + x

Combine like terms: -1x + -3x = -4x
2.4 = 6 + -4x + x + x

Combine like terms: -4x + x = -3x
2.4 = 6 + -3x + x

Combine like terms: -3x + x = -2x
2.4 = 6 + -2x

Solving
2.4 = 6 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
2.4 + 2x = 6 + -2x + 2x

Combine like terms: -2x + 2x = 0
2.4 + 2x = 6 + 0
2.4 + 2x = 6

Add '-2.4' to each side of the equation.
2.4 + -2.4 + 2x = 6 + -2.4

Combine like terms: 2.4 + -2.4 = 0.0
0.0 + 2x = 6 + -2.4
2x = 6 + -2.4

Combine like terms: 6 + -2.4 = 3.6
2x = 3.6

Divide each side by '2'.
x = 1.8

Simplifying
x = 1.8

See similar equations:

| -7y=-7/11 | | -7v=7 | | -9y+6=-2(y-8) | | 6p^2-3p-30=0 | | (x+14x)(x+14x)=52 | | 25=7(y+3)-3y | | 6x-21=2x+31 | | 15.5x=5.25x+256.25 | | 5p+8=16+4p | | T-3+4=3(3t-9) | | 5p+8=16+49 | | 7x=27+2x | | 3y+2=-17-3y | | 5x-15=3x-33 | | 11x=8x-8 | | -9x-16=20 | | 5u=4u-8 | | 7(x+1,2)=56,7 | | 4x^3/0.423 | | (4x^3)/(0.65)^2 | | 2(3x)+2(3x+2)=164 | | 5+7x=-2x+41 | | r/2+5r=11 | | 2/3x=10/13 | | 7+x=-3x+55 | | 6m-11.6=4m+8.2 | | 6*(1/7) | | 1.6(2.8)3x=6(4.5)x | | 5/3b=20 | | 6*1/7 | | (3-6i)-(4+5i)-(-5+i)= | | 4x+20=6x+200 |

Equations solver categories